Transcriptome analysis reveals reduced immunity and metabolic level under cold stress in Mauremys mutica - OuYang, Jiahui; Gao, Yangchun; Wei, Yufeng; Huang, Huangping; Ge, Yan; Zhao, Jun; Gong, Shiping (Frontiers in Marine Science, 2023)
The yellow pond turtle (Mauremys mutica) is widely cultured for food, medicine and for keeping as pets in China. The high risk of disease outbreaks and mortality caused by sudden sharp temperature drop events has significant negative effects on the aquaculture industry of M. mutica. However, the mechanism underlying the damage caused by cold stress is still unclear. To fill this gap, we performed transcriptome sequencing of M. mutica samples collected at three sampling time points (3h, 24h and 48h) during cold treatment, and at a recovery time point (96 h after the end of cold stress). The results showed that immunity and metabolism-related pathways (neuroactive ligand-receptor interactions, cytokine-cytokine receptor interactions and NOD-like receptor signaling pathways) were significantly enriched at both 24h and 48h. The expression of immunity and metabolism-related genes (BS2A1, PIWIL2 and Fads1) significantly decreased at all-time points compared to the control group. These results suggested that impaired immunity and depressed metabolism under cold stress may be the main cause of the massive cold-stress mortality of M. mutica. This study provides novel insights into the molecular mechanisms underlying mass disease and mortality caused by sudden sharp temperature drop events in M. mutica.